THE EFFECTIVENESS OF DEMINERALIZED BONE MATRIX AUGMENTATION ON RABBIT MANDIBULAR OSTEOBLAST DENSITY AFTER INCISOR EXTRACTION - Regina T. C. Tandelilin (Faculty of Dentistry, Universitas Indonesia, 2015)
The bone defect due to tooth extraction can be preventively managed by adding powder of bone graft intended for augmentation, which eventually induces the formation of new bones. This wound healing in hard tissue is preceded by the presence of osteoblast, which is the bone-lining cell responsible for the production of the bone matrix constituents. The objective of this study was to determine the effectiveness of the powder of demineralized bone matrix (DBM) after extraction of incisor in the rabbit alveolus mandibular bone on the osteoblast density. Twenty-four male rabbits aged 2.5 to 3.0 months weighed 900 to 1,100 grams were randomly divided into two groups. The treated rabbits were augmented with DBM after the incisor extraction on mandible. The mucosa was then sutured On the other group, the controlled rabbits received similar treatments with those of the treated rabbits except there was no augmentation of DBM. Decapitation of treated and controlled rabbits was made on day 5, 7, 10 and 14 days post surgery, each with three rabbits. Mandibles were cut, decalcified, and planted in paraffin block. The staining was done using HE. Significant differences in the density of osteoblast were noted on day 5, 7, 10 and 14 days post surgery, indicating that powder DBM successfully generates the new bone by osteoconduction.